Not a happy family [compact disc, unabridged] : a novel - Lapeña, Shari, 1960- (Penguin Random House Audio, 2021)
"Brecken Hill in upstate New York is an expensive place to live. You have to be rich to have a house there, and Fred and Sheila Merton certainly are rich. But even all their money can't protect them when a killer comes to call. The Mertons are brutally murdered the night after a fraught Easter dinner with their three adult kids. Who, of course, are devastated. Or are they? They each stand to inherit millions. They were never a happy family, thanks to their vindictive father and neglectful mother, but perhaps one of the siblings is more disturbed than anyone knew. Did someone snap after that dreadful evening? Or did another person appear later that night with the worst of intentions? That must be what happened. After all, if one of your family were capable of something as gruesome as this, you'd know"--Back cover.